Analisis Customer Relationship Management terhadap Kepuasan Pasien Pusat Jantung Nasional Harapan Kita - Liawatimena, S.; Arifianto, Teguh; Saliu, Yunina; Salim, Hartono Agus (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
The research tries to find out how big the influence of Customer Relationship Management of Heart Centre Patient Harapan Kita concerning the patient satisfaction. The Customer Relationship Management divide into three main functions which is Acquisition, Enhance, and Retain. The conclusion is, if there is increased in Customer Relationship Management of Heart Centre Patient Harapan Kita, it will increased the patient satisfaction also.